2023
DOI: 10.1186/s40479-023-00212-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of traumatic childhood experiences on interoception: disregarding one’s own body

Abstract: Background Deficient interoception, the processing and perception of internal bodily signals, has been discussed as a mechanism underlying various mental disorders. First results indicate a mediating role of interoception in the interplay of traumatic childhood experiences and adult mental disorders. Traumatic childhood experiences may hinder the adequate processing, integration, and trust in bodily signals that are important in order to understand and regulate own needs and emotions, thereby i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 110 publications
(106 reference statements)
1
4
0
Order By: Relevance
“…Decreased functional connectivity of the vestibular system with the PI in PTSD patients has been linked to weakened interoceptive awareness that subsequently may impede multisensory integration and facilitate a disengagement from their environment (Harricharan et al, 2017). This is in line with findings of body dissociation mediating the association between traumatic childhood experiences and emotional dysregulation (Schmitz et al, 2023).…”
Section: Sensory Integration and Interoceptionsupporting
confidence: 57%
See 1 more Smart Citation
“…Decreased functional connectivity of the vestibular system with the PI in PTSD patients has been linked to weakened interoceptive awareness that subsequently may impede multisensory integration and facilitate a disengagement from their environment (Harricharan et al, 2017). This is in line with findings of body dissociation mediating the association between traumatic childhood experiences and emotional dysregulation (Schmitz et al, 2023).…”
Section: Sensory Integration and Interoceptionsupporting
confidence: 57%
“…In individuals with childhood maltreatment, decreased cardiac interoceptive accuracy after acute social stress or pharmacologically induced noradrenergic activation has been observed (Schaan et al, 2019;Schulz et al, 2022). However, another study was unable to find similar effects of childhood maltreatment on interoceptive measures besides body dissociation (Schmitz et al, 2023). When presented with negative emotional cues, female patients with PTSD showed increased reactivity in more posterior regions of the insula compared to controls that may mirror an interaction between an exaggerated generation of interoceptive anxiety cues and heightened anxiety symptoms (Bruce et al, 2013).…”
Section: Sensory Integration and Interoceptionmentioning
confidence: 99%
“…Similarly, early traumas appear to disrupt an individual's ability to sustain a connection with their internal states, yielding significant repercussions in later adulthood [ 40 ]. Consistently, neuroimaging studies have underscored the impact of exposure to TCEs in neural impairments in the interoceptive network, especially in the insula, medial prefrontal cortex and subcortical structures [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the interoceptive configuration depends on the quality of synchronization in the attachment relationship established with the caregiver [ 39 ]. Similarly, recent findings have highlighted how TCEs can affect an individual's ability to stay connected with one’s own internal states [ 40 ]. In parallel, the extent to which an individual is able to detect and interpret body signals has been considered to influence the formation of emotional experiences and their regulation [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, research has emerged to explore the elements that have an effect on individual interoceptive ability. A recent study revealed that early life traumatic experiences may alter individual emotion regulation capacities by influencing their interoceptive functions (e.g., interoceptive sensibility) ( 125 ). Therefore, further research is necessary and beneficial for the study of MDD to explore the shaping and development of individual interoception throughout the lifespan and its influencing factors, as well as to delve deeper into the dynamic role of the brain insula in it.…”
Section: Discussionmentioning
confidence: 99%